Implementation of Puskesmas Pregnancy and Complication Prevention Program (P4K) as Implementation of SDGs at Healthcare Facilities: a Systematic Literature Review - Dewi Rokhmah; Tasya Lukita Cyndi Pradana; Heruddin; Nur Aziza Wahdaliya (Ficco Public Health Journal, 2025)
Background: Maternal Mortality Rate (MMR) remains a global issue wich is in line with the third SDGs, Indonesia having the third highest MMR in ASEAN at 189 per 100,000 live births. To reduce MMR, Indonesia implements the Childbirth Planning and Complication Prevention Program (P4K), but there are still many shortcomings that require further study on the factors affecting its implementation. Methods: The research method uses a Systematic Literature Review. Journal search terms are formulated using the PICO(S) framework. The literature search in this study used two databases, namely the National Library and Google Scholar. Results: The research results showed that 7 out of 10 articles explained that the successful implementation of the program was caused by the communication skills of midwives as health service providers, human resources, budget, dispositions and policies, bureaucracy and standard operational procedures, facilities and infrastructure. Meanwhile, the 3 articles explained stated that the success of the program was caused by the knowledge, attitudes and family support of pregnant women. Conclusions: The program's success is mainly attributed to factors like midwives' communication skills, resources, budget, policies, and infrastructure, while a smaller focus is placed on the knowledge, attitudes, and family support of pregnant women.